The problems of biopollution with jet fuels and the way of achieving solution - Boychenko, Sergey; Shkilnuk, Irina; Turchak, Vladimir (Transport, 2008)
The article considers and presents the classification methods of identifying and assessing petroleum biological contamination and techniques in maintaining biological stability of hydrocarbon fuel. The article focuses on analysis, arrangement and classification of the methods for identifying petroleum biological contamination and maintaining microbiological stability of hydrocarbon fuels.First published online: 27 Oct 2010